2010 ADA standards for accessible design with commentary (BNi Building News, 2012)
"This all-inclusive guide puts both the '2010 ADA standards for accessible design, ' which governs the construction and alteration of places of public use, together with the Department of Justice's 'Guidance on 2010 ADA standards for accessible design," in one complete book"--Page 4 of cover